Decrease of sialic acid residues as an eat-me signal on the surface of apoptotic lymphocytes - Meesmann, Hanna Marie; Fehr, Eva-Marie; Kierschke, Sonja; Herrmann, Martin; Bilyy, Rostyslav; Heyder, Petra; Blank, Norbert; Krienke, Stefan; Lorenz, Hanns-Martin; Schiller, Martin (Journal of cell science, 2010)
The silent clearance of apoptotic cells is essential for cellular homeostasis in multicellular organisms, and several mediators of apoptotic cell recognition have been identified. However, the distinct mechanisms involved are not fully deciphered yet. We analyzed alterations of the glycocalyx on the surfaces of apoptotic cells and its impact for engulfment. After apoptosis induction of lymphocytes, a decrease of α2,6-terminal sialic acids and sialic acids in α2,3-linkage with galactose was observed. Similar changes were to be found on the surface of apoptotic membrane blebs released during early stages of apoptosis, whereas later released blebs showed no impaired, but rather an increased, exposure of sialic acids. We detected an exposure of fucose residues on the surface of apoptotic-cell-derived membrane blebs. Cleavage by neuraminidase of sialic acids, as well as lectin binding to sialic acids on the surfaces, enhanced the engulfment of apoptotic cells and blebs. Interestingly, even viable lymphoblasts were engulfed in an autologous cell system after neuraminidase treatment. Similarly, the engulfment of resting apoptotic lymphocytes was augmented after neuraminidase treatment. However, the engulfment of resting viable lymphocytes was not significantly enhanced after neuraminidase treatment. Our findings support the importance of the glycocalyx, notably the terminal sialic acids, in the regulation of apoptotic cell clearance. Thus, depending on cell type and activation status, changes in surface glycosylation can either directly mediate cellular engulfment or enhance phagocytosis by cooperation with further engulfment signals.
Gesehen am 12.04.2023